2021
DOI: 10.1016/j.ijid.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and associated risk factors of selected zoonotic viral hemorrhagic fevers in Tanzania

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 70 publications
5
16
0
Order By: Relevance
“…Available statistics indicate that Buhigwe is among the districts with high malaria prevalence (24%) in Tanzania [14,37]. Moreover, a recent seroprevalence study has reported a 4.4% overall prevalence of VHF in the same district, the highest rate reported in Tanzania [4]. Co-infections due to malaria and either RVF or CCHF were most prevalent in Kinondoni district.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Available statistics indicate that Buhigwe is among the districts with high malaria prevalence (24%) in Tanzania [14,37]. Moreover, a recent seroprevalence study has reported a 4.4% overall prevalence of VHF in the same district, the highest rate reported in Tanzania [4]. Co-infections due to malaria and either RVF or CCHF were most prevalent in Kinondoni district.…”
Section: Discussionmentioning
confidence: 98%
“…Co-infections due to malaria and either RVF or CCHF were most prevalent in Kinondoni district. The district is within the high malaria burden region [37] and a recent study has reported an overall prevalence of VHF of 2.8% [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Viral haemorrhagic fevers (VHF) have become more prevalent in sub-Saharan Africa during recent years, causing either sporadic or large-scale epidemics, thus posing significant risk to public health. The VHFs reported in sub-Saharan Africa in recent years include Crimean-Congo haemorrhagic fever (CCHF), Ebola virus disease (EVD), Lassa fever (LF), Marburg virus disease (MVD), Rift Valley fever (RVF), and yellow fever (YF) [ 1 – 4 ]. On the other hand, malaria is among the most important mosquito-borne parasitic endemic disease in the region, accounting for 94% of the reported cases globally [ 5 ].…”
Section: Introductionmentioning
confidence: 99%